KELAYAKAN TEORETIS MEDIA KOMIK MATERI FILUM ARTHROPODA UNTUK KELAS X SMA - REZHA RIZQY NOVITASARY (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Joyful learning can be performed by using appropriate media and learning resources. Comic is a visual media which contain of illustration, text, color, and paragraph that joined in a plot of story. The purposes of this research were to develop comic Arthropoda as educational media in grade X Senior High School and to describe theoretical feasibility of comic based on the expert’s validation. This research was development research which used 4D models, which consisted of four steps, namely define, design, develop, and disseminate. However, the step of disseminate was not be done. The result showed that the theoretical feasibility got average scores 3,77 (very good). Key words: joyfull learning, comic arthropoda, 4D models, Senior High School Grade X